If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -3 = y + 2 Reorder the terms: -3 + 3y = y + 2 Reorder the terms: -3 + 3y = 2 + y Solving -3 + 3y = 2 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. -3 + 3y + -1y = 2 + y + -1y Combine like terms: 3y + -1y = 2y -3 + 2y = 2 + y + -1y Combine like terms: y + -1y = 0 -3 + 2y = 2 + 0 -3 + 2y = 2 Add '3' to each side of the equation. -3 + 3 + 2y = 2 + 3 Combine like terms: -3 + 3 = 0 0 + 2y = 2 + 3 2y = 2 + 3 Combine like terms: 2 + 3 = 5 2y = 5 Divide each side by '2'. y = 2.5 Simplifying y = 2.5
| -x^2+9=18 | | 30x+33y=2100 | | a+2b+10=28 | | x^2+5x-12=8x-2 | | 50x+24y=2400 | | x(2x^2+7x-4)=0 | | 3/5z=36 | | (2-3)(2+1)=0 | | 6(z-3)=z+4-2z | | 1/2(8x-7)=2/3(15x-12) | | ln(4x+5)=2lnx | | 2*(2+x)*5=70 | | 16x-2=8(2x-1) | | 3-2a+3=0 | | 4y+2(-3y-7)=-10-6y | | -3x-7/3=11/3 | | 8*what=560 | | 86=2l-44 | | -3x(-7/3)=11/3 | | -3(x)-7/3=11/3 | | (-3-1)(-3-1)=0 | | a(t)=6sinx | | (-3x-1)(-3x-1)=0 | | 164=110-v | | -3x(-7/11)=11/3 | | (x+2)*(x+2)=x*2+6 | | 7x+4-13x=-1+2 | | x^2+18x+22=-8 | | y-2x=500 | | g^2=-11g-28 | | (4x)+(x+90)=180 | | -3x-7/11=7/11 |